2014
DOI: 10.1016/j.drugpo.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of exclusion: Street drinking, gentrification and contests over public space

Abstract: The geographical exclusion of street drinkers that has occurred as a result of these laws warrants the consideration of a more socially responsible strategy than the current legislative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…The racial geography of a neighborhood appears to play an important role in shaping arrest disparities, which may in turn maintain segregation in those same neighborhoods (7). This mechanism is likely twofold: Police officers are more likely to stop or arrest Black individuals in White neighborhoods, but White residents may also be more likely to perceive the presence or actions of Blacks as suspicious and summon police(14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The racial geography of a neighborhood appears to play an important role in shaping arrest disparities, which may in turn maintain segregation in those same neighborhoods (7). This mechanism is likely twofold: Police officers are more likely to stop or arrest Black individuals in White neighborhoods, but White residents may also be more likely to perceive the presence or actions of Blacks as suspicious and summon police(14).…”
Section: Discussionmentioning
confidence: 99%
“…The mass incarceration of Black men resulting from this bias in drug related arrests has contributed to the social and economic destabilization of Black communities, increased STI risks for incarcerated men and their partners, and perpetuated racial health disparities (4-6). Advocates and qualitative research have suggested that racial inequity in drug related arrests may play a role in driving neighborhood segregation or creating space for gentrification efforts (7, 8). However, to date little research has examined whether the racial composition of a neighborhood is associated with elevated risk of drug related arrest among Blacks in the US.…”
Section: Introductionmentioning
confidence: 99%
“…As with cities like London and San Francisco, many households in cities like Melbourne and Sydney find it increasingly difficult to access affordable accommodation, which generates more generalized forces of systemic exclusion and sorting in the housing stock. Ambitions to create familiar strategies for urban renewal, creativity and pacification, associated with gentrification in other locales, have also been part of the landscape of recent empirical assessments of key changes in Australia's cities (Atkinson and Easthope 2009;Pennay, Manton, and Savic 2014). In this context, gentrification has been promoted by some local authorities, often indirectly through the courting of higher income residents, yet the high costs of housing in cities like Melbourne and Sydney has also driven moderate and high-income households to consider cheaper areas.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the scale and nature of implementation is variable within and between countries (O'Sullivan, 2012), such strategies have been widely documented in North America (Evans, 2012;Gaetz, 2013;NLCHP, 2014;Walby & Lippert, 2012), Central America (Godoy, 2012), Europe (Doherty et al, 2008;FEANTSA, 2007FEANTSA, , 2012Fernandez Evangelista, 2013) and KEYWORDS Homelessness; begging; street drinking; social control; force; coercion ARTICLE HISTORY Australasia (Adams, 2014;Laurenson & Collins, 2007;Pennay et al, 2014). In the USA, these interventions are so commonplace that the National Coalition for the Homeless developed and published a list of the ten 'meanest' cities based on the number and severity of ordinances affecting street homeless people, amongst other criteria 1 (NCH, 2006).…”
Section: Introductionmentioning
confidence: 99%